GAMIFICATION FOR EARLY CHILDHOOD USING ‘LINGOKIDS’ APPLICATION - Muhibuddin Fadhli (Universitas Muhammadiyah Ponorogo, 2018)
The introduction of language can start at an early age, although English is not a language that must be mastered in Indonesia. However, introducing this language for early childhood will not be an incorrect choice. This article discusses the application of Lingokids thoroughly in various countries. Data obtained by document analysis and literature were then analyzed using qualitative narative-descriptive method.There are some results from document and literature studies in some non-English countries. This application has become one of the applications used in English introduction.